2017
DOI: 10.1007/s10911-017-9374-y
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Models of Breast Cancer Share Amplification and Deletion Events with Human Breast Cancer

Abstract: Breast tumor heterogeneity has been well documented through the use of multiplatform –omic studies in human tumors. However, there is no integrative database to capture the heterogeneity within mouse models of breast cancer. This project identifies genomic copy number alterations (CNAs) in 600 tumors across 27 major mouse models of breast cancer through the application of a predictive algorithm to publicly available gene expression data. It was found that despite the presence of strong oncogenic drivers in mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…For instance, significant gene-expression heterogeneity has been observed in both MMTV-Myc and MMTV-Met transgenic mice, with noted similarity to human breast cancer [ 84–86 ]. Moving past gene expression, the same data have been used to predict copy number alterations across numerous transgenic mouse models, revealing potential driver events shared between mouse and human breast cancer [ 87 ]. In addition to the basic characterization of the mouse models, recent studies have shown a promising role for transgenic mice in development of treatment.…”
Section: Development Of New Targeted Therapies and Beyondmentioning
confidence: 99%
“…For instance, significant gene-expression heterogeneity has been observed in both MMTV-Myc and MMTV-Met transgenic mice, with noted similarity to human breast cancer [ 84–86 ]. Moving past gene expression, the same data have been used to predict copy number alterations across numerous transgenic mouse models, revealing potential driver events shared between mouse and human breast cancer [ 87 ]. In addition to the basic characterization of the mouse models, recent studies have shown a promising role for transgenic mice in development of treatment.…”
Section: Development Of New Targeted Therapies and Beyondmentioning
confidence: 99%
“…Expanding upon these findings with additional tumor models and samples, numerous reports have documented mouse and human counterparts at the level of gene expression [ 8 12 ]. In addition, copy number variation at the chromosome [ 13 ]and gene level [ 14 ]has been predicted from expression data and examined similarity to human breast cancer. The gene level CNV predictions demonstrated that chromosomal alterations were associated with histological subtypes[ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, copy number variation at the chromosome [ 13 ]and gene level [ 14 ]has been predicted from expression data and examined similarity to human breast cancer. The gene level CNV predictions demonstrated that chromosomal alterations were associated with histological subtypes[ 14 ]. With gene expression similarities to human breast cancer, a critical need remains to address how the tumor histology of mouse mammary tumors is related to gene expression programs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies published in recent years have compared genetically engineered breast cancer mouse model tumor transcriptomes with human disease (25)(26)(27), delineated disease progression observed in the mouse (28), and provided characterization of murine cell line orthotopic injection models (11). Here, we have expanded these efforts to interrogate MSGE in 18 different models of metastatic breast cancer, including cells in culture, intravenous injection and orthotopic implantation of cells, and GEMMs.…”
Section: Discussionmentioning
confidence: 99%